Similar deamination activities but different phenotypic outcomes induced by APOBEC3 enzymes in breast epithelial cells - Granadillo Rodríguez, Milaid; Wong, Lai; Chelico, Linda (Frontiers in Genome Editing, 2023)
APOBEC3 (A3) enzymes deaminate cytosine to uracil in viral single-stranded DNA as a mutagenic barrier for some viruses. A3-induced deaminations can also occur in human genomes resulting in an endogenous source of somatic mutations in multiple cancers. However, the roles of each A3 are unclear since few studies have assessed these enzymes in parallel. Thus, we developed stable cell lines expressing A3A, A3B, or A3H Hap I using non-tumorigenic MCF10A and tumorigenic MCF7 breast epithelial cells, to assess their mutagenic potential and cancer phenotypes in breast cells. The activity of these enzymes was characterized by γH2AX foci formation and in vitro deamination. Cell migration, and soft agar colony formation assays assessed cellular transformation potential. We found that all three A3 enzymes had similar γH2AX foci formation, despite different deamination activity in vitro. Notably, in nuclear lysates the in vitro deaminase activity of A3A, A3B, and A3H did not require digestion of cellular RNA, in contrast to A3B and A3H in whole cell lysates. Their similar activities in cells nonetheless resulted in distinct phenotypes where A3A decreased colony formation in soft agar, A3B decreased colony formation in soft agar after hydroxyurea treatment, and A3H Hap I promoted cell migration. Overall, we show that in vitro deamination data does not always reflect in cell DNA damage, all three A3s induce DNA damage, and the impact of each is different.